Relationship between Environmental Financial Accounting Practices and Corporate Financial Risk: Evidence from Listed Companies in Vietnams Securities Market - Soa, Nguyen La (Asian Economic and Financial Review, 2019)
This research assesses the relationship between the level of environmental financial accounting practices (EFAP) and corporate financial risk (CFR). Data was collected from companies listed on Vietnam’s securities market for five years from 2013 to 2017. The sample included two groups of companies: one, which followed EFAP and second which did not follow these practices. Based on quantitative research method, this study measured the relationship between levels of EFAP and CFR. The results reveal a close relationship between the EFAP and CFR levels of the current year and that of the following years(s). In addition, the results also point out that, there is a difference in financial risk between both the groups. The study recommends that enterprises should strengthen the environmental financial accounting practices to prevent financial risks in order to gain competitive advantage.